Imaging modification of colon carcinoma cells exposed to lipid based nanovectors for drug delivery: a scanning electron microscopy investigation. Issue 38 (15th July 2019) - Depalo, Nicoletta; Fanizza, Elisabetta; Vischio, Fabio; Denora, Nunzio; Laquintana, Valentino; Cutrignelli, Annalisa; Striccoli, Marinella; Giannelli, Gianluigi; Agostiano, Angela; Curri, Maria Lucia; Scavo, Maria Principia
Abstract : Imaging of soft nanostructure/cell interactions on surface cell membranes. Abstract : The adsorption at cell surfaces and cell internalization of two drug delivery lipid based nanovectors has been investigated by means of Field Emission Scanning Electron Microscopy (FE-SEM) operating at low beam voltage on two different colon carcinoma cell lines, CaCo-2 and CoLo-205, that were compared with the M14 melanoma cell line, as a reference. The cells were incubated with the investigated multifunctional nanovectors, based on liposomes and magnetic micelles loaded with 5-fluorouracil, as a chemotherapeutic agent, and a FE-SEM systematic investigation was performed, enabling a detailed imaging of any morphological changes of the drug exposed cells as a function of time. The results of the FE-SEM investigation were validated by MTS assay and immunofluorescence staining of the Ki-67 protein performed on the investigated cell lines at different times. The two nanoformulations resulted in a comparable effect on CaCo-2 and M14 cell lines, while for CoLo 205 cells, the liposomes provided an cytotoxic activity higher than that observed in the case of the micelles. The study highlighted the high potential of FE-SEM as a valuable complementary technique for imaging and monitoring in time the drug effects on the selected cells exposed to the two different nanoformulations.